2023
DOI: 10.1007/s00726-023-03334-w
|View full text |Cite
|
Sign up to set email alerts
|

Common pathogenic bacteria-induced reprogramming of the host proteinogenic amino acids metabolism

Xiao-yue Li,
Zi-xin Zeng,
Zhi-xing Cheng
et al.

Abstract: Apart from cancer, metabolic reprogramming is also prevalent in other diseases, such as bacterial infections. Bacterial infections can affect a variety of cells, tissues, organs, and bodies, leading to a series of clinical diseases. Common Pathogenic bacteria include Helicobacter pylori, Salmonella enterica, Mycobacterium tuberculosis, Staphylococcus aureus, and so on. Amino acids are important and essential nutrients in bacterial physiology and support not only their proliferation but also their evasion of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…Along with the undebatable physiological benefits inherent to amino acids (AAs) [46], which were long considered simply building blocks for protein synthesis [46], it has recently been shown that AAs act not only as growth-promoting substrates for pathogenic bacteria and opportunistic pathogens, but they also support the bacteria evasion that occurs in host immune defense [47]. Therefore, as in the case of saccharides, the profile and concentrations of individual free amino acids in V. opulus extracts were specified for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the undebatable physiological benefits inherent to amino acids (AAs) [46], which were long considered simply building blocks for protein synthesis [46], it has recently been shown that AAs act not only as growth-promoting substrates for pathogenic bacteria and opportunistic pathogens, but they also support the bacteria evasion that occurs in host immune defense [47]. Therefore, as in the case of saccharides, the profile and concentrations of individual free amino acids in V. opulus extracts were specified for the first time.…”
Section: Discussionmentioning
confidence: 99%